Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien - Utami, Amelia Tri; Ismanto, Hadi; Lestari, Yuni (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
The purpose of this study was to determine the effect of service quality dimensions of service quality are tangibles, reliability, responsiveness, assurance and empathy toward patient satisfaction. The sample used in this study is 100 respondents. The sampling method used purposive sampling and accidental sampling. Data collection used questionnaires. Data analysis method used quantitative analysis using validity and reliability test, F test, the coefficient of determination, t test and linear regression analysis. Based on the results of this study showed that the quality of service that consists of tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) simultaneously significant effect on patient satisfaction. Partially, Tangibles variable (X1), Reliability (X2) and Empathy (X5) showed significant effect on satisfaction (Y). While, variable Responsiveness (X3), Assurance (X4) partially did not show significant effect on satisfaction (Y).